TYPES OF ACTIVITIES - THE EFFECTS OF ENRICHING COGNITIVE FUNCTIONS DURING ADULTHOOD (Academia Science Repository, 2023)
Age: an annoying burden or an invaluable acquisition. Ancient doctors distinguished xenium and senectus to describe old age. In modern terminology, the first corresponds to the deficit model, the second corresponds to the competence model of old age. Its success or failure depends on biological, psychological, social and mental determinants. In the article, the determinants of personality are compared in terms of competence and scarcity, success and failure. And also the selected substantive aspects of biological life that are important for successful aging are outlined, namely: awareness of the transitory nature of life, attention to life, reconciliation with oneself, a higher state of health by F. Nietzsche, attention to God and humor.